The Metapleural Secretion of Acromyrmex laticeps (Forel) does not have Fungicide Effect on the Entomopathogenic Fungus Beauveria bassiana (Bals.) Vuill - Junqueira, Luciane Kern; Diehl, Elena (EntomoBrasilis, 2014)
The metapleural gland (MPG) is an exocrine structure, exclusive to formicids, being more developed in females and workers. This structure is stunted or nonexistent in males. Several possible functions for the secretion produced by this gland have been suggested, but a protection against entomopathogens is the most accepted hypothesis. To test this, we applied a suspension of spores (1.30 x 106) of Beauveria bassiana (Bals.) Vuill. on the MPG and the antero-superior portion of the metathorax (ASM) of winged females of Acromyrmex laticeps (Forel). We only applied the suspension in the ASM of males, since they do not have the atrium characteristic in the MPG. Our results indicated that the metapleural secretion of females has no fungicidal effect on B. bassiana, and therefore both males and winged females are sensitive to this entomopathogenic fungus. Ausência de Efeito Fungicida da Secreção Metapleural de Acromyrmex laticeps (Forel) Contra Beauveria bassiana (Bals.) Vuill. Resumo. A glândula metapleural (GMP) é uma estrutura exógena, encontrada apenas nos formicídeos, sendo mais desenvolvida nas fêmeas e operárias, enquanto nos machos ou está atrofiada ou não existe. Tem sido sugerido várias possíveis funções para a secreção produzida por esta glândula, sendo a hipótese de efeito protetor contra entomopatógenos a mais estudada. Para testar esta hipótese, foi aplicada uma suspensão de conídios (1,30 x 106) de Beauveria bassiana (Bals.) Vuill. nas GMP e na porção ântero-superior do metatórax (ASM) de fêmeas aladas de Acromyrmex laticeps (Forel), enquanto nos machos a suspensão foi aplicada apenas na porção ASM, pois estes não apresentam o átrio característico da GMP. Os resultados obtidos indicaram que a secreção metapleural das fêmeas desta espécie não possui efeito fungicida sobre B. bassiana, e que tanto os machos como as fêmeas alados são sensíveis a este fungo entomopatogênico.